Albright for A.S.B. Secretary campaign promotion - Gus Beck::::::photographer:::
Two students and two calves sit before a sign which reads 'Which twin has the Toni? We, Daisy and Maisy Coeds of Cal-Poly were born on April 10th. We hear that Jack Albright is running for A.S.B. Sec. We are both pulling for Albright, so is Mom and Pop. Why don't You! *Incidentally, Daisy Has the Toni.'